Designing dynamic circuit response - Feucht, Dennis (Feucht, Dennis. Analog circuit design series, 2010)
"The Analog Circuit Design set reduces the concepts of analog electronics to their simplest, most obvious form which can easily be applied (even quantitatively) with minimal effort. The emphasis of the set is to help you intuitively learn through inspection how circuits work and apply the same techniques to circuits of the same class. This second volume, Dynamic Circuit Response builds upon the first volume Amplifier Circuits (see related titles below) by extending coverage to include reactances and their time- and frequency-related behavioral consequences. Retaining a design-oriented analysis, this volume begins with circuit fundamentals involving capacitance and inductance and lays down the approach using s-domain analysis. Additional concepts and perspectives fill in the blanks left by textbooks in regards to circuit design. It simplifies dynamic circuit analysis by using the graphical methods of reactance plots. Methods of compensating amplifiers, including feedback amplifiers, are kept as simple as possible using reactance plots and s-domain transfer functions that mainly require algebraic skill."--Publisher's website.